A Commentary on the Development of the Neo-Latin Vocabulary with Reference to Recent Linguistic Studies - Krukowska, Sylwia (Collectanea Philologica, 2025)
The practical use of Latin is uncommon in the 21st century. Since the collapse of the Roman Empire, it has been considered a ‘dead language’. The main reason for this is that there is no nation for which Latin is a mother tongue. However, there are still people who can speak Latin fluently in everyday communication. Thus, we can ask ourselves where this idea originated and how it is possible to speak an ancient language in modern times. The aim of this paper is to briefly describe the history of Latin’s development, focusing on the coining of vocabulary related to breakthrough discoveries after the collapse of the Roman Empire. This should lead to answering the question of whether the continuous interest in Latin and its growth throughout the centuries was a natural evolution of the language or rather an artificial attempt to keep it alive. Furthermore, it is also worth considering whether it is appropriate to refer to Latin as a ‘dead language’ in every sense of the word. To support the thesis of Latin’s continuous growth, several lexical examples with word-formation analysis will be provided, demonstrating that the analogical processes observed within Latin also appear in modern languages.